On the use of Monetary and Macroprudential Policies for Small Open Economies - Ozkan, F. Gulcin (IMF Working Papers; Working Paper ;, 2014)
We explore optimal monetary and macroprudential policy rules for a small open economy. Delegating 'lean against the wind' squarely to macroprudential policy provides a more robust policy mix to shock uncertainty-(i) if macroprudential measures exist, there are no significant welfare gains from monetary policy reacting to credit growth under a financial shock; and (ii) monetary responses to financial markets could generate bigger welfare losses than macroprudential responses under different shocks. The source of outstanding liabilities also plays a role in the choice of policy instrument- macroprudential policies are particularly effective for emerging markets where foreign borrowing is sizeable.